Uma arca das tradições: educar e comemorar no Museu Mariano Procópio - Costa, Carina Martins (2011)
This thesis is a reflection on the making o Brazilian History writings in museums since the 1920s, a central moment for the establishment of a republican 'pedagogy of nationality' based on museal support. Some of the political-pedagogic efforts of those institutions were observed in order to understand the chief characteristics of an educational paradigm for historical knowledge in museums. Thus, the analysis of civic celebrations, guides and expositions allowed an approximation of the memorial activations of museum actors, with special attention to the continuities, negotiations and transformations o the projects, particularly in their pedagogic dimension. Mariano Procópio Museum was chosen as a case study both due to its specificities, which leads us to understand the 'concert' of national museums from the countryside, and to the relevance of its collection and the intensity of educational actions developed under the Geralda Armond management (1944-1980). The Armond management in the center of this thesis, marked by the defense of institutional continuity and of the framing of the Lage family memory; by the struggle of the material maintenance of the museum, with a close approximation to the civilian and military regime; and by the search for the professionalization of personnel and for dynamism in actions. The results highlight the multiplicity and fragility of the museum’s identity formation, associated to the fact that it is a 'municipal' museum. A situation which explains, at least in part, its oblivion in the national scene, despite its expressive collection and its articulation with the school system, through the strengthening of the civic sense of its pedagogic actions.